Quality of life and functional capacity of elderly people residents in rural area - Darlene Mara dos Santos Tavares; Sebastião Augusto Gávea Junior; Flávia Aparecida Dias; Nilce Maria de Freitas Santos; Paula Beatriz de Oliveira (Rev Rene)
This is a cross sectional household survey that aimed to measure the quality of life (QOL) of rural elderly from Uberaba-MG. It describes the functional capacity and determines their associated factors. 850 elderly people participated in the survey in which semi-structured instruments WHOQOL-BREF and WHOQOL-OLD were used. We conducted a descriptive analysis: chi-square and multiple linear regressions (p<0.05). Most of the subjects were male (52.8%), 60|-70 years old (60.6%), married (67.3%), 4|-8 years of study, individual income of a minimum wage (48.1%), retired for age (39,6%), housewife (39.3%) and homeowners (68.9%). The QOL scores were lower in the environment domain (63.31) and social participation facet (68.01). As for the basic activities of daily living, 99.8% were independent. As for lack of schooling, the higher age and greater number of co morbidities were associated to functional disability to perform the instrumental activities of daily living. Functionality of the elderly must be stimulated and strategies for organization and expansion of social activities must be created.